Dekanat szadkowski i jego dziekani w latach 1660-1763 - Zabraniak, Sławomir (Biuletyn Szadkowski, 2013)
The Szadek deanery, which covered an area of approximately 1,680 km2, was the largest within the Archdeaconate of Uniejow. It Was established rather early - at the beginning of the 16th century. In 1720, there Were 24 parishes and two affiliated churches. Visitation records from 1683-1763 show a decline in the Catholic population of the parishes of this deanery. Only a few of them experienced demographic growth. The percentage of the Jewish population, however, increased significantly. War, diseases and impoverishment were factors contributing to changes in the social fabrics in terms of occupations, religious beliefs and ethnic composition in the territory of the aforementioned deanery. This was the context in which the deans of the Szadek deanery conducted their pastoral activities. They were responsible for the pastoral care of and the faithful and the clergy in their parishes. Names of the deans of the Szadek deanery can be found on pages of the Uniejow consistory. Their personal signatures are also contained in visitation records and metrical books. On this basis, it can be concluded that deans were usually appointed from among the parish priests of lager parishes, who enjoyed a high level of respect, trust and esteem granted by both fellow priests and the Ordinary. They were often elderly priests with vast pastoral experiences. The office of the dean was generally associated with the provostry in Widawa and the presbytery in Rusiec.